A força dos precedentes na interpretação das normas gerais tributárias compensatórias - Caballero, Gregório Vizotto (2024)
In light of the evolution of the legal system and the current procedural system, which judicial precedents have been valued as a representative source of certainty and as a promoter of legal expectations, this paper’s main objective is to propose a reinterpretation of the normative content of the article 170-A of the Código Tributário Nacional (“CTN”) [Brazilian National Tax Code] when the decision, that recognized a credit in favor of the taxpayer, is based on a precedente of the Brazilian Superior Courts – Federal Supreme Court and Superior Court of Justice –, judged under the appeals representative of the controversy system, and therefore the requirement regarding the certification of the final and unappealable judgment of the individual claim is a mere procedural formality